2021
DOI: 10.1099/mgen.0.000513
|View full text |Cite
|
Sign up to set email alerts
|

From genotype to phenotype: adaptations of Pseudomonas aeruginosa to the cystic fibrosis environment

Abstract: Pseudomonas aeruginosa is one of the main microbial species colonizing the lungs of cystic fibrosis patients and is responsible for the decline in respiratory function. Despite the hostile pulmonary environment, P. aeruginosa is able to establish chronic infections thanks to its strong adaptive capacity. Various longitudinal studies have attempted to compare the strains of early infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 169 publications
(536 reference statements)
2
44
0
Order By: Relevance
“…Changes in the CF gut environment are likely to affect not only which microbes are present but also the metabolic potential and genomic content of the microbes that do thrive. Genetic and metabolic adaptation of opportunistic pathogens to the CF lung environment has been extensively documented ( 171 173 ), but very few studies have examined such features in the CF gut. One study demonstrated that E. coli from the CF gut have adapted to the high fat environment, as evidenced by increased growth rate and reduced stress response with glycerol as a sole carbon source ( 174 ).…”
Section: Moving Forwardmentioning
confidence: 99%
“…Changes in the CF gut environment are likely to affect not only which microbes are present but also the metabolic potential and genomic content of the microbes that do thrive. Genetic and metabolic adaptation of opportunistic pathogens to the CF lung environment has been extensively documented ( 171 173 ), but very few studies have examined such features in the CF gut. One study demonstrated that E. coli from the CF gut have adapted to the high fat environment, as evidenced by increased growth rate and reduced stress response with glycerol as a sole carbon source ( 174 ).…”
Section: Moving Forwardmentioning
confidence: 99%
“…The loci associated with alarmone ( spoT ), LPS ( pagL ) or alginate biosynthesis ( algG , algU ) and the master regulator gacA exhibited at least twofold higher d N / d S values in the collection of isolates from CF lungs than in those from other habitats. These loci are known to be key for P. aeruginosa to establish its lifestyle in CF airways [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…P. aeruginosa senses S. aureus secreted products and upregulates metal-and metaboliterelated pathways. We focused on the response of P. aeruginosa to S. aureus cell-free supernatant, as opposed to a co-culture model, since P. aeruginosa produces antimicrobials that may kill and lyse S. aureus cells (29,42,43), thus affecting the relative levels of staphylococcal secreted products that may be present. To determine the response of P. aeruginosa PA14 to S. aureus JE2, we performed RNA-seq on early-log phase P. aeruginosa cultures at 20 min, 1 h, and 2 h after the addition of 25% (v/v) S. aureus spent media or the same volume of media as a control.…”
Section: Resultsmentioning
confidence: 99%